Diseño e implementación de un arrancador suave para motores de inducción trifásicos - Mora-Ramírez, José Alejandro (Instituto Tecnológico de Costa Rica. Escuela de Electrónica, 2009)
Currently, the inefficiencies in the electromechanical processes lead to losses of money, reflected in the energy bill. One of these inefficiencies is the starting current in induction motors. The induction motors are the most common source of mechanical energy in the world, so the waste is found in all areas of the productive sector. These high currents not only raise the energy bill, but also cause damage to the equipment associated with the motors. In many cases the operator of the plant knows the problem, but the high cost or complexities of the methods for starting induction motors avoid the problem to be resolved. Against this background the company Enertec Soluciones raises the idea of developing a simple, economical and efficient device, to provide a soft start for induction motors. The idea is to attack the factor of "Peak Demand" of the electric bill with an affordable solution for small and medium enterprises. What is intended is to develop a system with Triacs, power controlled rectifiers, to progressively apply the voltage to motor terminals. This is important because if we manage to reduce the voltage it reduces the peak current at the starting of the motor.
Proyecto de Graduación (Licenciatura en Ingeniería Electrónica). Instituto Tecnológico de Costa Rica. Escuela de Ingeniería Electrónica, 2009.
Keywords: Motor de Inducción; Arranque Suave; Ahorro energético; Induction Motors; Soft Start; Energy Savings